Incidencia de la actividad física-recreativa en el desarrollo motriz de los niños y niñas del Centro de Educación inicial el Mamey del cantón Babahoyo 2015 - Soliz Arreaga, Diana Katiusca (2016)
Physical activity is a set of movements of the body in a planned way and repetitive improvement and helps to maintain one or more aspects of the physical condition. The effects of physical inactivity in children are those that lead to present problems of health, by which arises the need to develop an investigation To help, to determine what impact has the Physical Activity-recreational in boys and girls of the center of Initial Education Mamey of Canton Babahoyo, through a field research in the same which was implemented the pyramid of games for the adequate development unit, the same that was used in each of the exercises applied in the development drive